Farmer-centered pesticide risk reduction education in Senegal: A novel, participatory approach - Mary L Halbleib; Berit Dinsdale (Journal of International Agricultural and Extension Education, 2023)
As pest pressures continue to intensify across Sub-Saharan Africa, many smallholder farmers are increasing their use of pesticides, including highly hazardous options, to meet the market demands for high-quality fresh produce. Many of these farmers, however, have not had access to pesticide risk reduction training or have participated in programs that have not enabled them to protect themselves and their families. Given the risks posed by dried and invisible though still toxic pesticide residues, new forms of information and realistic learning strategies are required. This study combined the innovative Adaptive Learner-Centered Education (ALCE) approach with the Farmer Field School (FFS) model to address the need for a rigorous pesticide risk reduction program. This hybrid method was piloted over two years in a project with smallholder farmers in the Niayes region of Senegal. The findings demonstrate that following a 12-week course, this novel approach enabled 20 farmer-facilitators to educate and train 236 other farmers to reduce their use of highly hazardous pesticides, select pesticides with shorter restricted re-entry intervals, and adopt protective mitigation practices. Through seasonal planning exercises, farmers operationalized new knowledge in ways that fit their crop production needs and protected themselves and their families. Because the ALCE-FFS process is grounded in community-based needs, it can serve as an appropriate educational design framework for practitioners working in a wide range of geographic, sociocultural, and political contexts.
Keywords: community needs; smallholder farmers; human health; behavior change; Adaptive Learner-Centered Education; Farmer Field School